Deformation of Intrasalt Beds Recorded by Magnetic Fabrics. Issue 12 (23rd December 2019) - Issachar, R.; Weinberger, R.; Alsop, G. I.; Levi, T.
Key Points: Magnetic fabrics are used to study the deformation and kinematics of thick intrasalt beds within the Sedom salt wall in the Dead Sea Basin Magnetic fabrics show tectonic imprints due to folding associated with passive diapirism Thick intrasalt beds are mechanically distinct from the flowing salt and preserve information on salt tectonic processes operating at depth Abstract: Intrasalt beds comprise sedimentary layers within a weak rock salt mass. Thick intrasalt beds (hundred meter scale) are common in salt structures, yet their internal deformation has not been investigated in detail as outcrops of such beds are rare. In this study, we explore the internal deformation of thick intrasalt beds exposed along the Sedom salt wall in the Dead Sea Basin. These beds are highly deformed and form a kilometer‐scale recumbent fold. We measured the magnetic fabrics from six sites along these beds. Magnetic fabrics reflect the preferred alignment of crystals and grain shapes and are a proven kinematic marker in deformed rocks. Our analysis shows that the magnetic fabrics are mostly controlled by the preferred orientation of clay minerals. The orientations of the principal susceptibility axes vary along the salt wall regardless of the specific rock type. Minimum susceptibility axes ( K 3 axes) are normal to bedding, whereas maximum susceptibility axes ( K 1 axes) are subparallel to bedding strike. We suggest that the magnetic fabrics were acquired by strain imposed at a necked region along a subsurface fault, together with folding during passive diapirism. Generally, the magnetic fabrics have not been influenced by the later stage of active diapirism, which led to emergent beds at the surface. Nevertheless, in sites from the upper limb of the recumbent fold, the magnetic fabrics were further deformed by folding at the base of a salt glacier. Our results demonstrate that thick intrasalt beds are mechanically distinct from the encasing flowing salt and preserve information on salt tectonic processes operating at depth. Plain Language Summary: Salt structures are generally associated with large amounts of deformation. We studied the deformation of thick intrasalt beds within the exposed Sedom salt wall in the Dead Sea Basin. Due to the solubility of rock salt, exposures of salt structures are very rare and, therefore, the Sedom salt wall offers a unique opportunity to study outcrops of thick intrasalt beds. These beds comprise thick sedimentary layers (~200 m) that are surrounded by rock salt. We investigate the microstructural deformation of the rocks by measuring the magnetic fabrics of samples from six sites in the intrasalt beds along the salt wall. Magnetic fabrics provide a kinematic marker, as they usually reflect the preferred alignment of crystals and grain shapes within a rock sample. We found that the thick intrasalt beds record deformation that was acquired in the subsurface at a necked region, when the beds were folded from horizontal to subvertical attitudes along a subsurface fault. At a later stages of vertical flow along the salt wall, which led to emergent beds at the surface, no internal deformation was developed. This study demonstrates that thick intrasalt beds are mechanically distinct from the encasing flowing salt and thereby preserve information on salt tectonic processes operating at depth.